Growth performance, carcass traits and digestive function of broiler chickens fed diets with graded levels of corn resistant starch. Issue 2 (3rd March 2020) - Liu, Y. S.; Zhang, Y. Y.; Li, J. L.; Wang, X. F.; Xing, T.; Zhu, X. D.; Zhang, L.; Gao, F.
ABSTRACT: 1. This study was conducted to assess the effects of graded levels of dietary corn resistant starch (RS) on growth performance, carcass traits, nutrient retention, digestive organ index, intestinal morphology, digestive enzyme activities, and mRNA expression of certain nutrient transporters in broiler chickens. 2. A total of 320, 1-d-old Arbor Acres broiler chickens were randomly assigned to five dietary treatments, with eight replicates of eight birds in each. These treatments included one corn-soybean control diet, a corn-soybean based diet containing 20% corn starch, and three diets supplemented with 4%, 8% and 12% RS by replacing corn starch with 6.67%, 13.33% and 20% of Hi-Maize 260® (identified as control, RS1, RS2, RS3 and RS4, respectively). The feeding period lasted 42 days. 3. Performance parameters including feed consumption, feed conversion, body weight gain and percentage of abdominal fat at d 42 of age, nutrient retention (including dry matter, fat, total starch and nitrogen free extract), and apparent metabolisable energy was measured from d 18 to 20 and d 39 to 41 and showed negative linear responses to increasing dietary RS level (P < 0.05). Birds fed the RS3 and RS4 diets showed higher relative weight of duodenum, jejunum and ileum, as well as lower villus height and villus height/crypt depth compared to the control (P < 0.05). The activity of pancreatic trypsin of birds at d 21 and 42 of age decreased linearly in response to the increase of dietary RS level (P < 0.01). There were linear changes in up-regulated mRNA expression of SGLT-1 and down-regulated mRNA expression of GLUT-2 with increasing proportion of RS at d 21 and 42 of age (P < 0.05), respectively. 4. It was concluded that feeding broilers with diets containing higher concentrations of RS impaired the development of small intestine, which resulted in lower apparent total tract retention of nutrients and poorer body weight gain, feed efficiency and carcass traits of broiler chickens.